The Burning Wire - Deaver, Jeffery (New York Simon & Schuster Audio, 2010)
Quadriplegic forensic criminologist Lincoln Rhyme and his partner, Amelia Sachs, engage in a two-day race against time when a twisted killer, exploiting the modern world's drive toward sustainable energy, uses an everyday energy source as a weapon.
Unabridged.
Compact discs.
Keywords: Rhyme, Lincoln (Fictitious character) -- Fiction; Police -- Fiction -- New York (State); Serial murderers -- Fiction; Audiobooks; Manhattan (New York, N.Y.) -- Fiction; Mystery fiction